A MEASUREMENT OF ELECTROWEAK EFFECTS IN THE REACTION E+E--]TAU+TAU- AT 35.0 AND 42.4-GEV - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; Martin, A; et al. (Springer-Verlag, 1989)
We report on total cross section and forward backward charge asymmetry measurements of the reaction e+e- → τ+τ- at centre of mass energies of 35.0 GeV and 42.4 GeV using the TASSO detector. Including previous data an analysis in terms of electroweak parameters of the standard model is presented, and lower limits on mass scale parameters of residual contact interactions are given. A combined analysis of electroweak couplings using all our results on leptonic reactions e+e-→l+l- has been performed. © 1989 Springer-Verlag.